Interleukin‐17 induces CC chemokine receptor 6 expression and cell migration in colorectal cancer cells. Issue 7 (July 2015) - Chin, Chih‐Chien; Chen, Cheng‐Nan; Kuo, Hsing‐Chun; Shi, Chung‐Sheng; Hsieh, Meng Chiao; Kuo, Yi‐Hung; Tung, Shui‐Yi; Lee, Kam‐Fai; Huang, Wen‐Shih
Abstract : The CC chemokine receptor 6 (CCR6) and its ligand CCL20 are involved in human colorectal cancer (CRC) carcinogenesis and can promote the progression of CRC. In addition, interleukin‐17 (IL‐17), produced by a T cell subset named "Th17, " has been identified as an important player in inflammatory responses, and has emerged as a mediator in inflammation‐associated cancer. However, the relevance of IL‐17 in the development and progression of CRC still remains to be explored. This study aimed to investigate the effect of IL‐17 on the cell migration of CRC cells. Human CRC HCT‐116 cells were used to study the effect of IL‐17 on CCR6 expression and cell migration in CRC cells. IL‐17 treatment induced migration of HCT‐116 cells across the Boyden chamber membrane and increased the expression level of the CCR6. Inhibition of CCR6 by small interfering RNA (siRNA) and neutralizing antibody inhibited IL‐17‐induced cell migration. By using specific inhibitors and short hairpin RNA (shRNA), we demonstrated that the activation of ERK and p38 pathways are critical for IL‐17‐induced CCR6 expression and cell migration. Promoter activity and transcription factor ELISA assays showed that IL‐17 increased NF‐κB‐DNA binding activity in HCT‐116 cells. Inhibition of NF‐κB activation by specific inhibitors and siRNA blocked the IL‐17‐induced CCR6 expression. Our findings support the hypothesis that CCR6 up‐regulation stimulated by IL‐17 may play an active role in CRC cell migration. J. Cell. Physiol. 230: 1430–1437, 2015. © 2014 Wiley Periodicals, Inc., A Wiley Company